Peningkatan Kesadaran Konsumsi Protein Hewani Melalui Kampanye Gizi di Desa Tanjungratu, Lampung - Shella, Karina Pramay; fadillah, muhammad; Riftyani, Nur Rahma; Trada, Arkaan Faruq; Rindiyani, Frans Siska; Berliana, Calista Rizky; adelia, Elsa; Mulyasari, Rahmi (Jurnal Mitrawarga, 2025)
Animal protein plays a crucial role in the growth and development of children, particularly in preventing stunting and enhancing intelligence and immunity. However, the consumption of animal protein in Indonesia remains relatively low compared to other countries. Nutrition campaigns have become a strategic effort to raise public awareness about the importance of animal protein for the health of future generations. This article discusses the experience of the Community Service Program (KKN) from the University of Lampung (Unila) in Tanjungratu Village, Katibung District, South Lampung Regency, in educating the local community about the significance of animal protein consumption. This study is based on observations, interviews with local residents, and the implementation of a nutrition campaign intervention program. The findings indicate that nutrition campaigns conducted through direct education, social media, and engagement with local stakeholders can significantly improve understanding and increase the consumption of animal protein among children and families.